2016
DOI: 10.1007/s13277-015-4710-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-378-mediated suppression of Runx1 alleviates the aggressive phenotype of triple-negative MDA-MB-231 human breast cancer cells

Abstract: The Runx1 transcription factor, known for its essential role normal hematopoiesis, was reported in limited studies to be mutated or associated with human breast tumor tissues. Runx 1 increases concomitant with disease progression in the MMTV-PyMT transgenic mouse model of breast cancer. Compelling questions relate to mechanisms that regulate Runx1 expression in breast cancer. Here, we tested the hypothesis that dysregulation of Runx1-targeting microRNAs (miRNAs) allows for pathologic increase of Runx1 during b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 78 publications
3
54
0
Order By: Relevance
“…Dysregulation of miRNAs is a major culprit of tumorigenesis in breast cancers because their loss leads to the increased expression of targeted genes, including oncogenes. For example, Browne et al [19] showed that miR-378-mediated suppression of Runx1 alleviated the aggressive phenotype of triple-negative MDA-MB-231 human breast cancer cells. Playing the role of cancer inhibitor, miR-20a-5p has been found to be downregulated in the majority of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of miRNAs is a major culprit of tumorigenesis in breast cancers because their loss leads to the increased expression of targeted genes, including oncogenes. For example, Browne et al [19] showed that miR-378-mediated suppression of Runx1 alleviated the aggressive phenotype of triple-negative MDA-MB-231 human breast cancer cells. Playing the role of cancer inhibitor, miR-20a-5p has been found to be downregulated in the majority of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that miR-378 has biological functions that can regulate a variety of tumor cells, including cell proliferation [24], migration and invasion [25], and drug resistance [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, microRNA-214 can directly target Sufu mRNA and compromise its function, which facilitates lung adenocarcinoma metastasis and the epithelial-mesenchymal transition (EMT), which are most likely attributed to deregulated Hh signalling (100). Shown here, microRNA-214 and microRNA-378 display tumour-promoting roles, whereas some studies reported tumour-suppressive roles in cervical and breast cancer cells (101,102), implying the intrinsic complexity of multi-cellular organisms and the considerable influence of the microenvironment on gene functions.…”
Section: Regulation Of Sufu At the Mrna And Protein Levelmentioning
confidence: 92%